DINAMIKA KADAR NITRIT OKSIDA SELAMA STIMULASI KARBONDIOKSIDA DAN COLD PRESSOR TEST PADA PASIEN MIGREN - Yudy Goysal, Amiruddin Aliah, Irawan Jusuf (NEURONA, 2013)
INTRODUCTION MIGRAINE HAS NOW BEEN ASSOCIATED WITH ISCHEMIC STROKE WHICH IS SUBCLINICALLY SCREENED BY AUTOREGULATION DYSFUNCTION ENDOTHELIAL DYSFUNCTION MAY BE A MECHANISM UNDERLYING THIS ASSOCIATIONTHE STUDIESHOWS THAT NITRIC OXIDE NORELEASE IS IMPAIRED IN MIGRAINE PATIENTS